Adult presentation of ALCAPA: Echo and CT diagnosis. Issue 7 (21st January 2018) - Kerut, Edmund Kenneth; Kogos, Philip G.; Anderson, Jason H.; Turner, Michael; Ascuitto, Robert; Ross‐Ascuitto, Nancy; Said, Sameh M.
Abstract : A healthy 20‐year‐old male presented with aborted sudden death. Both thoracic echocardiography and cardiac computed tomographic angiography demonstrated the characteristic findings of ALCAPA noting a dilated and tortuous right coronary artery, dilated coronary collateral arteries within the interventricular septum or along the surface of the heart, and visualization of the left coronary artery origin from the posterior aspect of the main pulmonary artery. Both imaging modalities demonstrated all three characteristic findings of this rare coronary anomaly and served as complementary imaging studies for surgical correction.